PENGUATAN LITERASI HUKUM DAN DIGITAL MELALUI EDUKASI PANGGILAN SIDANG ELEKTRONIK (E-SUMMONS) PADA MASYARAKAT DESA JIREK MAS - Syaiful Bakri; Muhammad Abrori; M. Aqil Fahmi Sanjani (DEVELOPMENT: Journal of Community Engagement, 2026)
The digitization of the judicial system through the implementation of electronic court summonses (e-summons) is part of efforts to modernize legal services with the aim of improving efficiency and access to justice. However, the implementation of e-summons faces serious challenges at the rural community level, especially among communities with limited digital literacy or technological illiteracy. This Community Service (PkM) activity aims to increase understanding of electronic court summonses (e-summons) among the community of Jirek Mas Village, which has limited technology proficiency. The method used is a descriptive qualitative approach with an educational-participatory model through stages of observation, legal socialization, simple technology education, simulation, and mentoring. Data was collected through observation, interviews, pre-test and post-test questionnaires, and activity documentation. The PkM results showed that before the activity was carried out, the majority of the community did not understand the meaning, delivery medium, or legal force of e-summons. After the education and mentoring activities, there was a significant increase in the community's understanding of all measured indicators. This activity proves that an educational-participatory approach is effective in increasing legal literacy and awareness among rural communities regarding the electronic court system. Thus, this Community Service Program contributes to supporting the implementation of inclusive court digitalization and strengthening access to justice for rural communities.